ANALISIS TINGKAT PENGGUNAAN TEKNOLOGI DALAM AKTIVITAS JUAL BELI DENGAN MENGGUNAKAN APLIKASI E-COMMERCE - nurfadillahnajwa nurfadillahnajwa; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (JEBS (Journal of Economic and Business Student), 2023)
Information system is a system created by humans in which there are hardware and software, the components of which are computer-based which are made to collect data, store data, and manage data. Information systems are very useful for a country and companies, especially large companies. which makes it very easy for them to achieve their desired goals. The development of information technology also affects the business world. With the development of information technology, the business world also develops. the development of this information system produces a system that makes it easier for consumers to meet their needs by using e-commerce or electronic commerce. This research provides benefits to us so that we know the level of use of information technology in conducting buying and selling activities through e-commerce applications such as shopee, tokopedia, Bukalapak, and others in this digital era.